THE IMPLEMENTATION OF CHARACTER EDUCATION TO THE DORMITORY STUDENTS OF â€œSMART INTERNATIONAL LANGUAGE COLLEGEâ€ IN PARE KEDIRI - Zumaroh, Ulfa (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This research aimed at one main purpose, how the implementation of character education in SMART’s Dormitory, particularly with regard to the students’ characters before staying in SMART’s Dormitory and the students’ characters right now. This research his designed descriptive qualitatively. It was conducted in the dormitory of Smart International Language College Pare Kediri. The data collection involved a number of instrument including observation, interview, and document. The data was analyzed using qualitative data analysis, they are; (1) data reduction including the data identification, data classification, and data codification, (2) data display and verification, (3) conclusion. The result of the analysis shows that there is the implementation of character education in SMART’s Dormitory. The implementation appears on (1) the students’ characters before staying in S’tory mostly were lack, (2) the implementation of character education is applied in S’tory, and (3) the students’ characters right now improves.